2012
DOI: 10.1080/15226514.2011.619235
|View full text |Cite
|
Sign up to set email alerts
|

Response Characteristics ofScirpus Triqueterand Its Rhizosphere to Pyrene Contaminated Soils at Different Growth Stages

Abstract: Scirpus triqueter (Triangular club-rush), a typical wetland species, is used to study the response characteristics to pyrene. A pot experiment was conducted to investigate the growth parameters (height, diameter, shoot number, total volume, underground biomass, above-ground biomass and total biomass), and enzymes (catalase and superoxide dismutase) of S. triqueter. The characteristics of soil enzymes (catalase and polyphenol oxidase) and microorganisms (bacteria and fungi) were also assessed after pyrene treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Scirpus is a rhizomatous perennial sedge native to China 37 . The plant may reach a height of about 20–100 cm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scirpus is a rhizomatous perennial sedge native to China 37 . The plant may reach a height of about 20–100 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Scirpus triqueter L. (hereafter called Scirpus ) is species native to China 37 . It grows on low-lying moist sites, where an overlapping niche exists with Spartina , and it likely results in competition between the two plant species.…”
mentioning
confidence: 99%
“…To some degree, the larger diesel removal extent in the V. tricolor rhizosphere might be induced by the more active soil microbes. As vital oxidoreductases in the soil, PPO and CAT are accountable for essential metabolic processes including the degradation and detoxification of xenobiotic pollutants . In this literature, it was observed that there was a positive correlation between pollutant removal extent and PPO activity ( p < 0.01) with regard to phytoremediation.…”
Section: Resultsmentioning
confidence: 98%
“…Soil microorganism activity was determined to speculate the phytoremediation efficiency. P. indica has been reported to inhibit the phytopathogens such as Fusarium graminirum infection to barley plant (Deshmukh et al 2007;Zhang et al 2012). Thereby it is reasonable to explain that because of the presence of P. indica, the microorganism activity in rhizosphere was lower than that in non-rhizosphere.…”
Section: Discussionmentioning
confidence: 97%